Effects of Transcutaneous Spinal Direct Current Stimulation (tsDCS) in Patients With Chronic Pain: A Clinical and Neurophysiological Study - Guidetti, Matteo; Ferrucci, Roberta; Vergari, Maurizio; Aglieco, Giada; Naci, Anisa; Versace, Sara; Pacheco-Barrios, Kevin; Giannoni-Luza, Stefano; Barbieri, Sergio; Priori, Alberto; Bocci, Tommaso (Frontiers in Neurology, 2021)
Background and aims: Chronic pain is a complex clinical condition, often devastating for patients and unmanageable with pharmacological treatments. Converging evidence suggests that transcutaneous spinal Direct Current Stimulation (tsDCS) might represent a complementary therapy in managing chronic pain. In this randomized, double-blind and sham-controlled crossover study, we assessed tsDCS effects in chronic pain patients. Methods: Sixteen patients (aged 65.06 ± 16.16 years, 8 women) with chronic pain of different etiology underwent sham and anodal tsDCS (anode over the tenth thoracic vertebra, cathode over the somatosensory cortical area - 2.5 mA, 20 min, five days for one week). As outcomes, we considered the Visual Analogue Scale (VAS), the Neuropathic Pain Symptom Inventory (NPSI), and the components of the lower limb flexion reflex (LLFR), i.e., RIII threshold, RII latency and area, RIII latency and area, flexion reflex (FR) total area. Assessments were conducted before (T0), immediately at the end of the treatment (T1), after one week (T2) and one month (T3). Results: Compared to sham, anodal tsDCS reduced RIII area at T2 (p=0.0043) and T3 (p=0.0012); similarly, FR total area was reduced at T3 (p=0.03). Clinically, anodal tsDCS dampened VAS at T3 (p=0.015), and NPSI scores at T1 (p=0.0012) and T3 (p=0.0015), whereas sham condition left them unchanged. Changes in VAS and NPSI scores linearly correlated with the reduction in LLFR areas (p=0.0004). Conclusions: Our findings suggest that tsDCS could modulate nociceptive processing and pain perception in chronic pain syndromes.